Ciprofloxacin Resistance in Enterococcus faecalis Strains Isolated From Male Patients With Complicated Urinary Tract Infection - Lee, Gilho (The Korean Urological Association, 2013)
PURPOSE: Urinary tract infection (UTI) is one of the most prevalent bacterial infections, and fluoroquinolone therapy is a well-known standard regimen for UTI. The prevalence and risk factor analysis of fluoroquinolone resistance in enterococcal UTIs are not well documented. The aim of this study was to evaluate the antimicrobial susceptibility and risk factors for ciprofloxacin resistance in Enterococcus faecalis strains isolated from patients with complicated UTI. MATERIALS AND METHODS: We evaluated 81 E. faecalis strains isolated from 81 male patients at a single teaching hospital over 3 years. The Vitek 2 automatic system was used for antimicrobial susceptibility analysis. RESULTS: Antimicrobial resistance rates were rare for ampicillin/sulbactam, imipenem, and vancomycin in E. faecalis. Forty-six percent of the E. faecalis strains were resistant to levofloxacin, 47% were resistant to ciprofloxacin, and 58% were resistant to norfloxacin. E. faecalis strains were highly resistant to erythromycin (92%) and ftetracycline (96%). The risk factor analysis revealed that age intervals, the underlying diseases, catheterization, and the number of admissions did not increase the risk of ciprofloxacin resistance, whereas patients with hospital-acquired infection (odds ratio [OR], 18.15; 95% confidence interval [CI], 3.46 to 95.13; p=0.001), patients who were treated in a urological department (OR, 6.15; 95% CI, 1.5 to 25.41; p=0.012), and patients who were transferred from health care centers (OR, 7.393; 95% CI, 1.32 to 41.22; p=0.023) had an increased risk of ciprofloxacin resistance compared with the matched controls. CONCLUSIONS: Ciprofloxacin is no longer a recommended therapy for E. faecalis from complicated UTI in men with risk factors. We suggest that ampicillin/sulbactam can be recommended as alternatives for treating ciprofloxacin-resistant E. faecalis strains associated with UTI in Korea.